Meningkatkan Aktivitas dan Kolaborasi Materi Kekayaan Budaya Indonesia Menggunakan Model PATIN Pada Siswa Sekolah Dasar - Dewi Rana Maghfirah; Noorhapizah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is the low level of activity, critical thinking skills and student collaboration. This is due to one-way learning, lack of student activity during learning, not using varied learning models and media, and monotonous learning. Efforts to overcome this are by using the PATIN model. The aim of this research is to describe teacher activities, analyze increases in student activity, critical thinking and collaboration skills, as well as learning outcomes. This research used PTK which was carried out in 4 meetings. The research subjects were 33 class IV students at SDN Alalak Tengah 4 Banjarmasin, in the second semester of the 2024/2025 academic year. This research uses a qualitative approach. Data was obtained through observing teacher activities, student activities, critical thinking and collaboration skills, as well as learning outcomes obtained through group and individual written tests. Analysis of the data presented is in the form of descriptions, tables and graphs. The research results showed that the teacher's activities at meetings 1 to 4 received "very good" criteria. Student activity at meetings 1 to 4 increased from the criteria "quite active" to "very active". Critical thinking skills at meetings 1 to 4 increased from the criteria of "less skilled" to "very skilled". Collaboration skills at meetings 1 to 4 increased from the criteria of "fairly skilled" to "very skilled". So this has an impact on the affective, summative and formative learning outcomes of students from meetings 1 to 4, where there is a classical increase. Based on the findings, it can be concluded that the PATIN model can improve teacher activity, student activity, critical thinking and collaboration skills, as well as student learning outcomes. It is recommended to use this model as an alternative in improving teacher activity, student activity, collaboration and critical thinking skills, as well as learning outcomes.